Electrodeposition, characterization and corrosion investigations of galvanic tin-zinc layers from pyrophosphate baths - Stopić, Milena D.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Tin-zinc alloy deposits are recognised as a potential alternative to toxic cadmium as corrosion resistant coatings. Tin-zinc alloy layers offer outstanding corrosion protection for steel by combining the barrier protection of tin with the galvanic protection of zinc. Tin-zinc coatings have been used on the chassis of electrical and electronic apparatus and on critical automotive parts such as fuel and brake line components. In this study, tin-zinc alloy deposits were successfully prepared from alkaline, pyrophosphate-based electrolytes. The plating process gives a compact and fine grained deposit. The desired proportions of tin and zinc in the deposited alloy are determined by the bath composition and the operating conditions during plating. Three electrode systems were used for the electrochemical investigation. The mechanism of Sn-Zn electrodeposition was studied by linear and cyclic voltammetry. The corrosion parameters, including open-circuit potential-time curves, corrosion potential and corrosion current density of electrodeposited tin-zinc alloys of different compositions have been examined in a brine medium containing 3 wt. % NaCl. The corrosion resistance depends on the plating composition. The Sn-28Zn deposit showed the best anticorrosive properties.